(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, Ayzenk determined the dependence on temperament in determining the influence of the individual psychological state on the game performance of young football players. The author explained the selection of attack, midfield, defense and goalkeepers for the game positions depending on the temperament of young players through experimental research.